Hubungan Antara Praktik Pemberian Makan dan Kedisiplinan Penimbangan Berat Badan dengan Kejadian Underweight pada Anak Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Pengasih II Kabupaten Kulon Progo - Laurensia Jhuliviany Jati Wibowo; Diyan Yunanto Setyaji; Ruth Surya Wahyu Setyaning (HB PRESS, 2025)
Underweight is a condition of malnutrition characterized by thin body weight or below normal. Parenting patterns related to feeding and weighing practices are one of the factors causing underweight. Poor nutritional status has an impact on growth disorders, low cognitive abilities and Intelligence Option values. This study aims to determine the relationship between feeding practices and weighing discipline with the incidence of underweight in toddlers aged 24-59 months in the working area of the Pengasih II Health Center, Kulon Progo Regency. The design of this study was cross-sectional. Data were obtained by interview using a questionnaire. The sampling technique was clustered random sampling. The number of research subjects was 176. Data analysis used descriptive analysis, Chi-square, and Binary Logistic Regression. There is a significant relationship between feeding practices (OR=2.256, p=0.023) and weighing discipline (OR=4.175, p=0.002) with the incidence of underweight in toddlers aged 24-59 months (p>0.05). The prevalence ratio of underweight in children aged 24-59 months is more often found in parents who are not disciplined in weighing their children every month and inappropriate feeding practices by parents in children. It can be concluded that there is a significant relationship between feeding practices and weighing discipline in children aged 24-59 months with the incidence of underweight.